Polymeric ionic liquids (PILs): effect of anion variation on their CO2 sorption - Bhavsar, Rupesh S.; Kumbharkar, Santosh C.; Kharul, Ulhas K. (Journal of Membrane Science, 2012)
A series of polymeric ionic liquids (PILs) based on poly(diallyldimethylammonium chloride), P[DADMA][Cl] as a precursor was investigated by varying anions categorized into carboxylates, sulphonates and inorganic type. For the exchange of chloride from P[DADMA][Cl] by another anion, silver salt of the corresponding anion was preferred. Obtained PILs were investigated for physical properties which are anticipated to affect gas sorption. PILs possessing carboxylate (especially acetate) anion exhibited attractive CO2 sorption capacity as well as sorption selectivity over H-2 and N-2, in Comparison to Other two Categories. PIL with acetate anion, P[DADMA][Ac] possessed appreciable CO2 sorption coupled with high selectivity (S-CO2/S-N2 = 114.3). This crucial finding from this series of PILs was further substantiated by making PIL based on poly(vinylbenzyltrimethylammonium chloride), P[VBTMA][Cl] as a precursor. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Anion exchange; CO2 sorption; Polymeric ionic liquid

Investigation of gas permeation properties of film forming polymeric ionic liquids (PILs) based on polybenzimidazoles - Bhavsar, Rupesh S.; Kumbharkar, Santosh C.; Kharul, Ulhas K. (Journal of Membrane Science, 2014)
Polymeric ionic liquids (PILs) are emerging as new generation membrane materials for CO2 separation. Gas permeation properties of a recently developed PIL family based on three structurally different polybenzimidazoles (PBIs) possessing excellent film forming characteristics are reported. Effects of cationic backbone and anions on gas permeation properties of PILs using pure gases (He, H-2, N-2, CH4, and CO2) were examined at 20 atm upstream pressure and correlated with their physical properties. In comparison to the parent PBIs, PILs exhibited generally higher CO2 permeability, without largely affecting CO2 based selectivity. Some of these PILs exhibiting high PCO2/PCH4, selectivity and P-H2/P-CO2, approaching similar to 1 indicated dominance of CO2 sorption over diffusion. The CO2 sorption specificity of these PILs was distinctly observed based on their improved S-CO2/S-N2, S-CO2/S-CH4 and S-CO2/S-H2 selectivity than their parent PBIs. A large variation in permeation properties of PILs based on a common polycation but different anions indicated that anions play a crucial role on governing gas permeation properties of these PILs. (C) 2014 Elsevier B.V. All rights reserved
Keywords: Gas permeation; Membranes for CO2 separation; Polybenzimidazole; Polymeric ionic liquid